IMPROVING THE METHODOLOGY FOR DEVELOPING STUDENTS' ANALYTICAL SKILLS THROUGH PROBLEM-BASED LEARNING (International journal of artificial intelligence, 2025)
This article explores the improvement of methodology aimed at developing students' analytical skills through problem-based situations. It highlights the importance of equipping students with critical thinking and problem-solving abilities in the context of modern education. The paper analyzes effective strategies for integrating problem-based learning (PBL) into English for Specific Purposes (ESP) classrooms and provides practical recommendations for teachers. Through the use of real-life scenarios and case studies, the article demonstrates how PBL fosters deeper understanding, independent thinking, and analytical reasoning among students.